Scanning transmission soft X-ray spectromicroscopy of mouse kidney and liver - Mansikkala Tuomas; Ohigashi Takuji; Salo Miia H.; Hiltunen Anniina E.; Vuolteenaho Reetta; Sipilä Petra; Kuure Satu; Huttula Marko; Uusimaa Johanna; Hinttala Reetta; Miinalainen Ilkka; Kangas Salla; et al. (Elsevier B.V., 2025)
Scanning transmission X-ray microscopy (STXM) in the soft X-ray range is well-suited to study ultrastructural features of mammalian soft tissues. Especially at the carbon 1s edge, the imaging contrast varies drastically across the edge due to rapid changes in the X-ray absorption cross-section of functional groups present in the tissue samples enabling label-free soft X-ray spectromicroscopic studies. We present STXM spectromicroscopic imaging of mouse kidney and liver tissues. We especially concentrate on ultrastructural abnormalities in genetically modified Slc17a5 mice. STXM is a promising technique to study storage diseases without chemical alteration due to staining agents, but sample preparation poses a challenge.